The Influence of Financial Literacy, Financial Inclusion, and Social Environment on the Decision to Use QRIS by "MSMEs" - Fadli Hadi Badjeber Hadi Badjeber; Uswatun Hasanah; Noval; Ibrahim R. Mangge; Muhammad Ikbal (Tazkia Islamic Finance and Business Review, 2026)
This study aims to analyze the influence of financial literacy, financial inclusion, and the social environment on the decision to use the Quick Response Code Indonesian Standard (QRIS) among Micro, Small, and Medium Enterprises (MSMEs) in Palu City. The background of this research is based on the still low adoption rate of QRIS among MSME actors, despite the government's efforts to promote payment digitalization programs. This indicates a gap between the availability of digital payment infrastructure and users' readiness to adopt it. This research uses a quantitative approach with a total of 100 respondents who are MSME actors in Palu City. Data was collected thru questionnaires and analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method to test the relationships between variables. The research results indicate that financial literacy does not significantly influence the decision to use QRIS, while financial inclusion and the social environment have a positive and significant impact. Simultaneously, these three variables positively and significantly influence the decision to use QRIS among MSME actors. This finding suggests that the decision to use QRIS is more influenced by ease of access to formal financial services and social support from the surrounding environment, compared to an individual's level of financial understanding. The results of this research are expected to provide input for the government and financial institutions in strengthening digital education and expanding financial inclusion to accelerate the adoption of digital payment systems in the MSME sector.